Apert Syndrome: orthopedic treatment - López López, Daniel; López López, Luis; Alonso Tajes, Francisco; Rosende Bautista, Carolina (Revista Internacional de Ciencias Podológicas, 2011)
Apert syndrome is an autosomal dominant disorder characterized by craniosynostosis, midfacial malformations and symmetric syndactyly of hands and feet. We present a case of a female Caucasian, 45 years old, prenatal diagnosis at 24 weeks gestation, apert syndrome type I, after sonography showing features deformity were observed characteristics. She refered pain at the first head of the first metatarsal of the left foot, long evolution that improves with rest and with the intake of oral analgesics, which is the realization of orthopedic treatment palie that the disease process.
Keywords: Acrocephalosyndactyly Type I; Craniosynostosis Syndactyly; Apert Syndrome